A transgenic mouse model mimicking human cardiac amyloidosis. (3rd October 2022) - Fauvel, C; Mulder, P; Heron, C; Nicol, L; Brakenhielm, E; Bellien, J; Kalopissis, A; Bauer, F
Abstract: Background: Heart failure (HF) pathophysiology complicating cardiac amyloidosis (CA) is poorly explored due to the lack of relevant animal model. A recently transgenic mouse expressing an amyloidogenic variant of human apolipoprotein AII was developed that showed ubiquitous amyloid deposit but limited data on cardiac involvement. Purpose: To investigate heart structure and function in transgenic mice expressing an amyloidogenic variant of human apolipoprotein AII Methods: Seventy-nine mice ageing 2 to 3 months were included in this study as follow: amyloidosis group (n=44) and sham (i.e. genetic mutation without phenotypic expression, n=35). Both were serially imaged by echocardiography (Vevo3100 Fujifilm) and cardiac magnetic resonance imaging (CMR, Biospec 4.7 tesla), and invasively explored by left–sided catheterization (pressure-volume loop [PV loop], Millar Catheterization), before sacrifice and histological investigations. Results: As soon as 2–3 months of age, the amyloidosis group demonstrated significant left ventricular (LV) hypertrophy, diastolic dysfunction and left atrial dilatation compared with sham group (p<0.01). Left ventricular ejection fraction was initially normal in both groups but deteriorated in amyloidosis mice (p<0.001) before right ventricular function collapses (p<0.001). In amyloidosis group, PV loops showed significant LV end-diastolic pressure increase (p<0.001), stiffer LV (p<0.01) and reduced systolic function LV elastance (p<0.05). Invasive and non-invasive abnormalities paralleled severe CA deposits and subendocardial fibrosis matrix remodeling, both labeling by Congo red and Red Sirius coloration (p<0.001). CMR analysis showed significant T1 (p<0.05) and T2 (p<0.01) signal increase and significant decrease in myocardial perfusion (p<0.01) in the amyloidosis group. Clinically, mice with amyloidosis covered less distance during exercise test (p<0.001) and died earlier (log-rank test, p<0.01). Conclusion: By mimicking human cardiac amyloidosis, the model of transgenic mouse expressing an amyloidogenic variant of human apolipoprotein AII is promising to investigate the underlying pathophysiology of heart failure due to amyloidosis. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Pfizer grant